CHARACTERIZATION OF THE STABLE AGGREGATES OF THE SOIL SPECIFIC TO THE NORTHERN PLATEAU OF THE REPUBLIC OF MOLDOVA - Maxim COROCHII; Ioan PĂCURAR; Marcel DÎRJA; Adela Hoble (Agricultura, 2019)
The importance of the aggregates studies could be presented from the following perspectives: elaboration of the soil studies to substantiate the projects of arrangement, organization and exploitation of the meadows; elaboration of (naturalistic) soil studies prior to the preparation of forestry arrangements; elaboration of the soil studies necessary to substantiate the projects of complex arrangement of the slopes in order to prevent and control erosion on agricultural land in non-irrigated regime; elaboration of the soil studies in order to recover the lands degraded by social-economic activities. The researches consists in highlighting the influence of the shelterbelts on the evolution of the soil in the immediate area of it, compared with the soil developed inside the shelterbelts, starting from the premise: degraded lands, recovered through shelterbelts, in order to ensure full protection of agricultural crops, it must also have a high degree of soil amelioration, a low risk of erosion and erosivity.